Letter from Federico Schnell to Max Bredig, September 20, 1943 - Schnell, Federico (1943)
Federico Schnell tells Max Bredig (1902-1944) that he no longer has a way to write to his brother, Alfred Schnell (1900-1944), and sister-in-law, Eva Schnell (1913-1944). Despite that, he does believe that they are still alive and have escaped deportation. Schnell ends the letter with some personal updates and wishes Bredig well.
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Federico; Schnell, Alfred, 1900-1944; Schnell, Eva, 1913-1944; World War (1939-1945); Political refugees